Bone tissue in different parts of the edentulous maxilla and mandible - Lindhe, Jan; Bressan, Eriberto; Cecchinato, Denis; Corrá, Enrico; Toia, Marco; Liljenberg, Birgitta (Clinical oral implants research, 2013)
Background The composition of the fully healed edentulous ridge of the posterior maxilla was recently examined and was found to contain about 50% mineralized bone and 16% bone marrow. Aim The objective was to examine the composition of the tissue of the fully healed ridge in different portions of the maxilla and the mandible in partially dentate subjects. Material and methods Eighty‐seven healthy subjects were included. A trephine drill was used to harvest hard tissue specimens. The biopsies were decalcified, embedded in paraffin, sectioned, stained, and examined using a point‐counting procedure. Results The marginal portion of the jaws almost consistently contained a cortical cap that was significantly wider in the mandible than in the maxilla and twice as wide in the anterior as in the posterior segments of the mandible. Lamellar bone and bone marrow were the dominating tissue elements. Lamellar bone occupied about 63% of the tissue in the mandible and 46% in the maxilla. The maxilla contained about 23% bone marrow as compared to 16% in the mandible. In the mandible, 70% (anterior) and 57% (posterior) were made up of lamellar bone. In the maxilla, the proportion of lamellar bone in the anterior and posterior segments was similar (about 45%). Bone marrow occupied close to 40% of the anterior maxilla, while in the posterior maxilla and the anterior and posterior mandible marrow comprised between 13 and 18%. Conclusion Marked differences existed with respect to tissue composition of the edentulous ridge between the maxilla and the mandible. The cortical crest was wider in the mandible than in the maxilla, and widest in the symphysis region of the mandible. The proportion of bone marrow was greater in the maxilla than in the mandible. The maxillary front tooth region was poor in lamellar bone but rich in bone marrow, while the anterior mandible contained large amounts of mineralized bone but small amounts of bone marrow.